Introduction to Islamic civilisation - Savory, Roger (Cambridge Cambridge University Press, 1976)
This book is a wide-ranging and general introduction to Islamic civilisation from its origins to the present day. Writing in clear and non-technical language, Professor Savory's contributors seek answers to broad and important questions: how did a single civilisation develop in a multi-ethnic, multi-cultural region; how did Islamic internationalism come to be translated into powerful nationalist movements in modern times; how has the West been affected by its continuing contact with Islam; what factors have threatened Islamic civilisation in modern times, and is there a future for it at all. The book begins with a section on the geographical, ethnic and linguistic background of the Middle East, continues with an historical re;sume; of the Islamic period, and moves on to the core chapters on the religious, philosophical and legal foundations of Islamic society and its contributions to world civilisation in the fields of literature, art, science and medicine. The time-scale covers the pre-Islamic, medieval and modern periods, and care has been taken to draw out the implications of the interaction between Christian West and Islamic East from the Crusades down to the massive encroachment of the West upon the Muslim world - at military, political, economic and cultural levels - in the modern era. Introduction to Islamic Civilisation is based on a successful series of adult-education programmes broadcast on Canadian radio, organised by members of the Department of Islamic Studies at the University of Toronto. The material has been revised and rewritten for book publication and is offered as a genuinely introductory handbook on a vital and fascinating subject.
Introduction to the Middle East / G.M. Wickens -- The historical background of Islamic civilisation / C.E. Bosworth -- Islamic faith / Charles J. Adams -- God and his creation : two medieval Islamic views / Michael E. Marmura -- Law and traditional society / R.M. Savory -- Arabic literature : a living heritage / Ella Marmura -- Persian literature : an affirmation of identity / G.M. Wickens -- Turkish literature through the ages / Eleazar Birnbaum -- Islamic art : variations on themes of arabesque / R. Sandler -- The Middle East as world centre of science and medicine ; What the West borrowed from the Middle East / G.M. Wickens -- Christendom vs. Islam : 14 centuries of interaction and co-existence / R.M. Savory -- The changing concept of the individual / R. Sandler -- The modern Arab world / L.M. Kenny -- Tribalism and modern society : Iraq, a case study / Albertine Jwaideh -- Iran / W. Millward -- Turkey : from cosmopolitan empire to nation state / Eleazar Birnbaum -- Khåatimah / G. Wickens.
Includes bibliographical references (p. 195-197) and index.
Keywords: Islamic civilization; Middle East -- Civilization